Biomechanical analysis of the Mawashi Geri Jodan kick in Karate-Do - Lino Michel Valdés Cabrera; Zelma Quetglas González; Rosa María Tabares Arévalos; Raúl Enrique Ruíz Viladón (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2020)
The current expectations of contemporary sport have imposed challenges that necessarily imply, from positions of science, the constant search for new technologies that will allow athletes to raise their sporting performance, from which karate-do has not been exempt. In the present research, a study of the biomechanical characteristics that contribute to the fulfillment of the technical pattern of the Mawashi Geri Jodan kick was carried out, with the objective of proposing the procedure for its analysis, considering the biomechanical indicators that guarantee its technical pattern. For this purpose, a sample of six athletes from the dojos of the Pinar del Río municipality was worked on, as well as a secondary sample of six coaches and eight specialists. Scientific research methods and techniques were used, such as analytical-synthetic, inductive-deductive, document analysis, observation, interview, videography, measurement and expert judgment. To achieve the purpose, a methodology was taken as reference, identifying the biomechanical characteristics that contribute to the result of this technique, which were complemented by the analysis of the deterministic model built. Once the biomechanical characteristics that make possible the successful implementation of this technique were selected, the quantitative analysis of the variables with their correspondence in the incidence of the result of the implementation of the technical movement through video recording was carried out by means of expert criteria. The determined biomechanical characteristics that appear in the deterministic model constructed for the technique, are feasible for the analysis of the quality of the execution of this kick.